Pengembangan Material Berbasis Multimedia Untuk Peningkatan Efektifitas Pengajaran Konsep Dasar IPA di PGSD S1 Universitas Almuslim - Afriadi Afriadi (Biologi Edukasi: Jurnal Ilmiah Pendidikan Biologi, 2011)
Lackness of motivation of PGSD S-1 Almuslim students to participate in Basic Science Concept 1 subject is caused by classical lecture with the method which is fail to activate students, as well as the use of abstract concept. The fact motivates the researcher to find solution to make students interested in learning Basic Science Concept 1 by developing multimedia based material through Macromedia Flash Mx. The research aimed to know the activity and studenst’ response in Basic Science Concept lecture by using multimedia based material to the students of PGSD S1 Almuslim. Qualitative and descriptive statistic are used to analysed the data. The result shows that the average of exam 1 is 72,32 increase to 78,00 at exam 2. Observation Data towards teaching activity shows that 83,16% has fit to teaching scenario. Observation Data towards students’ activity shows the average score 85,71% good chategory. Students give positive response to all aspects with the range of 79 – 97%. As a conclusion, the use of interractive multimedia based material could improve teaching effectivity to Basic Science Concept lecture. Finally, it is recommended that lecturers should apply interractive multimedia based material in other subjects as a teaching model at PGSD S1 Almuslim.